Trienamines for the Organocatalytic Synthesis of Nitrogen-Containing Heterocycles - Cano, Jessica R. Gutiérrez; López, Julio; Vázquez, Miguel A.; Cruz, David C.; Gómez, Clarisa Villegas (Current Organic Chemistry, 2019)
Nitrogen-containing heterocycles (NCH), constitute an important group of molecules, which are widely extended in whole chemical space. These compounds are of great interest due to their diverse biological activities. Currently, many compounds derived from NCH are used as powerful drugs for the treatment of diseases ranging from bactericides to anticancer agents. During last decade, the enantioselective synthesis of numerous heterocyclic compounds has been achieved through the use of chiral organocatalysts. The present contribution explores the application of the aminocatalysis towards the synthesis of NCH, particularly through the trienamine catalysis.
Keywords: aminocatalysis